CL degradation of Y2SiO5:Ce thin films coated with SnO2 - Coetsee, Elizabeth (University of the Free State, 2006)
The degradation of the cathodoluminescence (CL) intensity of cerium-doped yttrium silicate (Y 2SiO 5:Ce) phosphor thin films and commercially available Y2SiO5:Ce phosphor powders from Phosphor technology, England, were investigated for possible application in low voltage field emission displays (FEDs). Thin films of Y2SiO5:Ce were pulsed laser ablated on Si (100) substrates by using a XeCl (308 nm) excimer laser, in an oxygen (O) ambient gas pressure of 7.5 x 10-4 Torr, with laser energy of 81.81 mJ, repetition rate of 10 Hz, substrate temperature of 400°C, target to substrate distance of 3.7 cm and by using 6600 pulses. Some of the phosphor thin films were coated with tin oxide (SnO2), with the same deposition parameters as for the Y2SiO5:Ce phosphor layer except for the amount of pulses that was reduced to 1200 pulses. A SnO2 layer was ablated onto some of the thin films in order to investigate the effect of the coated layer on the surface and on the degradatio n of the CL intensity. Rutherford backscattering (RBS) was used to measure the film thicknesses. The results showed a non uniform Y2SiO5:Ce layer covered with a 58 nm thick SnO2 layer. Scanning electron microscopy (SEM), atomic force microscopy (AFM) and energy dispersive spectroscopy (EDS) were use to study the surface morphology of the thin films. The results indicated that the Y2SiO5:Ce phosphor was ablated onto the Si (100) substrate surface as micron-sized spherical particles and that the SnO2 layer was ablated as a uniform coated layer covering the surface of the substrate and the randomly distributed spherical Y2SiO5:Ce particles. SEM was also use to study the surface morphology of the Y2SiO 5:Ce phosphor powders and the results showed that the particles were agglomerated. X-ray diffraction (XRD), that was used to measure the crystal planes of both the thin films and the powders, revealed the monoclinic crystal structure of Y2SiO5:Ce. Auger electron spectroscopy (AES), X-ray photoelectron spectroscopy (XPS) and CL spectroscopy were used to monitor changes in the surface chemical composition and luminous efficiency of the Y2SiO5:Ce phosphor powders and thin films (coated and uncoated) . AES and CL spectroscopy measurementswere done with 2 keV energy electrons and with beam current densities between 26.3 mA.cm-2 and 52.63 mA.cm-2 , in high vacuum and in oxygen pressures of 1 x 10-8, 1 x 10-7 and 1 x 10-6 Torr. AES indicated adventitious carbon (C) on the surface before CL measurements were made. C was depleted from the surface during electron bombardment. Residual gas mass analysis (RGA) showed that C was removed from the surface as volatile gas species. RGA with the electron beam on resulted in a higher intensity of CO2, CO and H2O gas specie s, compared to when the electron beam was off. This is consistent with the electron stimulated surface chemical reaction (ESSCR) model, whereby the electron beam dissociates the oxygen gas species into reactive atomic species, which then reacts with the carbon on the surface to form the volatile CO2 and CO gas species. Auger peak to peak heights (APPH) for oxygen and silicon on both the uncoated thin film and the powder surface stayed almost constant. The CL intensity (measured at 440 nm) increased within the first 300 C.cm-2, which is the result of the depletion of the carbon from the surface, and then it stayed constant for prolonged electron bombardment. The carbon results in an extra layer on the thin film surface that increases the energy loss of the incoming electrons. This results in the creation of fewer electron – hole pairs for photon emission during radiative recombination. The CL emission spectrum resulted in the characteristic double shoulder peak of Y2SiO5:Ce with the two main peak positions at 440 and 500 nm (blue light) before and after 24 hr s of electron bombardment for the uncoated thin film, coated thin film and for the powders. Light emission in the rare earth, Ce3+, is due to the 5d ? 4f transition due to the splitting effects of the 4f energy level. The 4f energy level splits due to the effect of the crystal field in Y2SiO5 as the host material, into the 2F7/2 and the 2F5/2 energy levels. The broad band emission of Y2SiO5:Ce is the result of the different splitting effects due to the crystal field. The relatively high CL intensity of the thin films is attributed to the spherically shaped phosphor particles grown on the surface of the Si (100) substrate. The SnO2 was also successfully ablated as a coating layer. The SnO 2 coating layer increases the energy loss of the incoming electrons which results in a lower CL intensity. The CL intensity for the uncoated thin film was therefore higher than for the coated thin film. The CL intensity stayed almost constant for the 24 hr s of electron bombardment of both the coated and uncoated thin films. The CL intensity for the phosphor powders, however, behaved differently. The intensity showed an increase after about 300 C.cm-2. The CL emission spectrum showed an increase in a second broad band at a wavelength of 650 nm after 24 hr electron bombardment. It was proved with XPS that this second broad band is due to the formation of a luminescent silicon dioxide (SiO2) layer on the surface of the Y2SiO5:Ce phosphor powders, as a result of the electron surface stimulated reactions (ESSCR). The increase in the CL intensity is thus due to the luminescent SiO2 layer that was formed as a result of electron beam irradiation that causes the Si-O bonds to break and to form intrinsic defects at 1.9 eV (650 nm) and 2.7 eV (459 nm). XPS also indicated that the Ce concentration on the surface layer increased during the degradation process and the formation of CeO2 and CeH3 also resulted from the degradation process. The phosphor powders degraded from a blue light emitting phosphor before electron bombardment to a whit ish light emitting phosphor after 24 hr, as a result of the luminescent SiO2 layer formed during degradation.
Dissertation (M.Sc. (Physics))--University of the Free State, 2006.
Keywords: Phosphors -- Biodegradation; Surface chemistry; Electrons -- Emission; SiO2; ESSCR; Coated layer; Cathodoluminescence; Y2SiO5:Ce